Tác động của rủi ro địa chính trị đến mức độ đầu tư của các doanh nghiệp phi tài chính niêm yết tại Việt Nam - Nguyễn Hữu, Mạnh; Phan Gia, Quyền (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2025)
This study examines the relationship between geopolitical risk (GPR) and the investment levels of non-financial listed firms in Vietnam during the period 2007–2022, while also assessing the role of information asymmetry. Utilizing the Entropy method to construct an index measuring the degree of information asymmetry, the results reveal that GPR does not reduce investment through capital expenditure cuts, contrary to previous studies. However, information asymmetry significantly influences investment decisions when GPR increases. Specifically, firms facing high levels of information asymmetry tend to reduce their investments, whereas firms with low levels of information asymmetry continue to maintain their investment projects despite geopolitical risks. Based on these results, the authors propose policy implications aimed at promoting investment and contributing to national economic growth.
Keywords: Geopolitical risk; Investment; Information asymmetry